2017
DOI: 10.3390/w9050317
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Iron Release during Riverbank Filtration

Abstract: At many sites, anoxic conditions and dissolution of iron and manganese are already present, or are likely to develop during riverbank filtration (RBF). A prediction of iron and manganese mobilization during riverbank filtration is required to evaluate the need for further water treatment. Different methods have been tested at RBF sites in Germany: water and sediment analysis, batch and column experiments using river water, sequential extraction, and the mass balance approach. At these sites, a "wash out" effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…At the same time, RBF is used for water quantity management. The interaction between surface water and groundwater (GW) prevents over-exploitation of the aquifer, salinisation by rising deep saline groundwater, and subsidence due to groundwater abstraction [4]. Against the background of the world's increasing demand for drinking water, RBF is also suitable as a low-cost treatment process with low technical requirements for developing countries [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, RBF is used for water quantity management. The interaction between surface water and groundwater (GW) prevents over-exploitation of the aquifer, salinisation by rising deep saline groundwater, and subsidence due to groundwater abstraction [4]. Against the background of the world's increasing demand for drinking water, RBF is also suitable as a low-cost treatment process with low technical requirements for developing countries [5].…”
Section: Introductionmentioning
confidence: 99%
“…A schematic diagram of processes affecting water quality during riverbank filtration and groundwater (GW)[4].…”
mentioning
confidence: 99%
“…Earlier column tests and studies at bank infiltration sites (e.g., Diem et al 2013;Greskowiak et al 2006;Grischek and Paufler 2017;Henzler et al 2016;Massmann et al 2006;Sharma et al 2012) have demonstrated an elevated DO consumption early along the infiltration flow path. The amount of DO consumption is temperature dependent, typically leading to anoxic conditions in the summer and aerobic conditions in the winter in the aquifer.…”
Section: Dissolved Oxygenmentioning
confidence: 99%
“…For example, to be able to predict the need for post-treatment to remove iron or manganese mobilized during riverbank filtration, insight is required in what determines the development of iron and manganese concentrations during operation (e.g., [27][28][29]). Such insight can be supported by field monitoring, e.g., by using isotopes to assess the relative contribution of different water types to the recovered water in mixed source MAR systems [20], reveal the mobilization of chromium during infiltration of a desert dune sand aquifer [2], to assess retention times [30], or to study factors that affect clogging by, e.g., air bubbles [19].…”
Section: Effective and Reliable Mar Operationmentioning
confidence: 99%
“…In addition to effective infiltration, an important aspect of the performance of MAR is the extent to which water quality improves or deteriorates during subsurface passage. The release of iron and manganese commonly occurs (e.g., [29]), resulting in post-treatment requirements and risks of abstraction well clogging. Therefore, the application of subsurface iron removal (SIR) is a promising technology to be combined with MAR [6,35].…”
Section: Enhancing the Performance Of Marmentioning
confidence: 99%